Implementation of Medicines Pricing Policies in Ghana: The Interplay of Policy Content, Actors' Participation, and Context - Augustina Koduah; Leonard Baatiema; Irene A. Kretchy; Irene Akua Agyepong; Anthony Danso-Appiah; Anna Cronin de Chavez; Timothy Ensor; Tolib Mirzoev (Kerman University of Medical Sciences, 2023)
Background  Implementing medicines pricing policy effectively is important for ensuring equitable access to essential medicines and ultimately achieving universal health coverage. However, published analyses of policy implementations are scarce from low- and middle-income countries (LMICs). This paper contributes to bridging this knowledge gap by reporting analysis of implementation of two medicines pricing policies in Ghana: value-added tax (VAT) exemptions and framework contracting (FC) for selected medicines. We analysed implications of actor involvements, contexts, and contents on the implementation of these policies, and the interplay between these. This paper should be of interest, and relevance, to policy designers, implementers, the private sector and policy analysts.Methods  Data were collected through document reviews (n = 18), in-depth interviews (IDIs) (n = 30), focus group discussions (FGDs) (n = 2) and consultative meetings (n = 6) with purposefully identified policy actors. Data were analysed thematically, guided by the four components of the health policy triangle framework.Results  The nature and complexity of policy contents determined duration and degree of formality of implementation processes. For instance, in the FC policy, negotiating medicines prices and standardizing the tendering processes lengthened implementation. Highly varied stakeholder participation created avenues for decision-making and promoted inclusiveness, but also raised the need to manage different agendas and interests. Key contextual enablers and constraints to implementation included high political support and currency depreciation, respectively. The interrelatedness of policy content, actors, and context influenced the timeliness of policy implementations and achievement of intended outcomes, and suggest five attributes of effective policy implementation: (1) policy nature and complexity, (2) inclusiveness, (3) organizational feasibility, (4) economic feasibility, and (5) political will and leadership.Conclusion Varied contextual factors, active participation of stakeholders, nature, and complexity of policy content, and structures have all influenced the implementation of medicines pricing policies in Ghana.